Moral Education and Social Attitudes of the Young Generation: Challenges for Indonesia and the International Community - Muhammad Bagaskara Rizqy Harmadi; Antonio Johan Adiguna; Dena Cahya Setia Putri; Nabila Banuati; Alamsyah Luhur Pambudi; Luqman Syarief Wicaksono Broto (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2022)
Currently, Indonesian people are often faced with the problem of juvenile delinquency, which is increasingly being heard in the mass media. The entry of foreign cultures greatly influences the Indonesian nation, especially for the millennial generation. External culture influences millennials in behaving that is not in accordance with Pancasila values, causes various kinds of juvenile delinquency such as promiscuity, and affects the loss of tolerance. The increasing prevalence of juvenile delinquency in this millennial era is also the aftermath of complex problems every year, one of which is the weakening of social control from the norms that apply in society plus a lack of awareness in interpreting the ideals of life of the nation contained in everything in pancasila. If this is not addressed immediately, it is not impossible that in the future this nation will be chaotic and colored by the rise of feuds and the loss of local culture. This must be addressed immediately, not only the government is required to tackle this phenomenon, but all communities, especially the millennial generation, must also participate in dealing with it.